The trials of seaweed Caulerpa racemosa cultivation using the off-bottom culture at The Kastela Waters, Ternate Island Districht, Ternate City - Koda, Dr. M. Irfan; Samadan, Gamal M.; Malan, Sudirto; Subur, Riyadi (Sangia Research Media and Publishing, 2021)
Seaweed of Caulerpa racemosa has bright prospects for cultivation. In North Maluku province in general, the cultivation of seaweed Caulerpa sp has never been developed, even though the waters of North Maluku have enormous potential, because this type of seaweed is scattered in various marine waters in North Maluku. One of the efforts that needs to be done is to carry out this type of seaweed cultivation in an optimal and sustainable manner.The seaweed Caulerpa racemosa cultivation unit used in this study was the off-bottom method measuring 5 m x 10 m. This size can contain 5 stretch ropes/risers with a length of 10 m and a distance of 1 m between the stretch ropes/risers. Each stretch / riser line contains about 45 seed clump points with a distance between clumps of 15 cm. The observation procedure for the growth of Caulerpa racemosa seaweed was carried out by weighing the seaweed seeds in each stretch/riser rope. The weight of seed that is weighed is the weight of seeds at the time of planting and the weight of seaweed at harvest.The results showed that the average growth rate of seaweed Caulerpa racemosa was varied for each rope. In ris 1 rope, the average absolute weight growth reached 100.88 grams, ropes 113.33 grams, ris rope 3, 88.00 grams, rope ris 4, 116.00 grams, and rope ris 5, amounting to 113, 33 grams. In general, the highest growth in absolute weight was found in the fourth rope, which was 116.00 grams.